2015
DOI: 10.1104/pp.15.01236
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic expression of WRI1 affects fatty acid homeostasis in Brachypodium distachyon vegetative tissues

Abstract: Triacylglycerol (TAG) is a storage lipid used for food purposes and as a renewable feedstock for biodiesel production. WRINKLED1 (WRI1) is a transcription factor that governs fatty acid (FA) synthesis and, indirectly, TAG accumulation in oil-storing plant tissues, and its ectopic expression has led to TAG accumulation in vegetative tissues of different dicotyledonous plants. The ectopic expression of BdWRI1 in the grass Brachypodium distachyon induced the transcription of predicted genes involved in glycolysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(85 citation statements)
references
References 102 publications
3
81
1
Order By: Relevance
“…A limited number of WRI1 genes identified from model plants, such as Arabidopsis for dicots (Cernac and Benning, 2004), B. distachyon for temperate grasses (Yang et al, 2015), and B. napus (Liu et al, 2010) and maize (Shen et al, 2010) for crops, have been tested for their ability to enhance the oil content in developing seeds and vegetative tissues (Grimberg et al, 2015). We tested the potential of each Camelina WRI1 isoform to enhance the vegetable oil biosynthesis in N. benthamiana leaves.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A limited number of WRI1 genes identified from model plants, such as Arabidopsis for dicots (Cernac and Benning, 2004), B. distachyon for temperate grasses (Yang et al, 2015), and B. napus (Liu et al, 2010) and maize (Shen et al, 2010) for crops, have been tested for their ability to enhance the oil content in developing seeds and vegetative tissues (Grimberg et al, 2015). We tested the potential of each Camelina WRI1 isoform to enhance the vegetable oil biosynthesis in N. benthamiana leaves.…”
Section: Resultsmentioning
confidence: 99%
“…Since WRI1 is a regulator for lipid accumulation even in non-seed tissues (Kilaru et al, 2015), WRI1 paralogs distinct from seed-specific WRI1 were observed in the tallow layer, the non-seed tissue, in Chinese tallow ( Triadica sebifera ), which is a valuable oilseed-producing tree (Divi et al, 2016). In yet another study, the ectopic expression of B. distachyon WRI1 isolated from the vegetative tissues induced an increase in TAG content and simultaneously resulted in cell death in the leaf blades (Yang et al, 2015). Ectopic expression of WRI1 s from diverse species and tissues in leaves of N. benthamiana has been shown to result in the production of TAG content ranging from 0.05 to 2.2%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[66] In maize and Arabidopsis, WRI1 regulates the genes involved in FA biosynthesis, such as ACCase subunits, ACP1, and KAS1, through direct binding to AW box in their promoter regions. [66,79,80] Arabidopsis PII plays a role in the fine tuning of fatty acid biosynthesis and is directly controlled by WRI1. An increase in FA production was accompanied by a maximal content of PII Arabidopsis.…”
Section: Wrinkledmentioning
confidence: 99%
“…It belongs to the AP2/EREB domain family and triggers the expression of genes involved in glycolysis and fatty acid synthesis (Cernac and Benning, 2004;Focks and Benning, 1998). Expression of maize homologs complementing the WRINKLED1 mutation in Arabidopsis and heterologous expression in leaf tissue of Arabidopsis have shown WRINKLED1 to have the capacity for complementation of deficiencies across species as well as to ectopically induce oil accumulation and heterologously enhance oil content in seeds (An and Suh, 2015;Pouvreau et al, 2011;Sanjaya et al, 2011;Yang et al, 2015). Recently, also protein structural properties have been investigated to elucidate and enhance the function of the WRINKLED1 transcription factor .…”
Section: Introductionmentioning
confidence: 99%